Continuous monitoring of critically ill patients using photoplethysmography—the road to a less invasive ICU monitoring - Rosinhas, João; Malheiro, Rui; Pimenta, João Tiago; Sá, Ricardo; Serdoura, Francisco; Paiva, José-Artur (Frontiers in Digital Health, 2025)
IntroductionIntensive Care Medicine is based on continuous timely monitoring of physiological variables to guide modulation of therapy. This monitoring is often invasive, but there is a trend for the adoption of non-invasive devices, already largely used in wards and homecare, to reduce risk of device-associated side effects. The aim of this study was to assess the accuracy of a non-invasive equipment (Corsano Cardiowatch 287-2B) in the assessment of blood pressure, heart rate, temperature and oxygen saturation in critically ill patients admitted to the ICU.MethodThis prospective cohort study developed in an adult ICU admitting patients for level 3 and 2 of care compared the Corsano Cardiowatch 287-2B with the ICU standard monitoring, namely continuous electrocardiogram, invasive arterial blood pressure through arterial catheter, pulse oximeter and central thermometer. Concordance was assessed using the Bland-Altman test.ResultsNineteen patients were included in the study. The number of time-points included for comparison between the two monitoring strategies were more than 50,000 in pulse and heart rate, around 40,000 in oxygen saturation and body temperature and 1,200 in systolic and diastolic blood pressure. Bias for heart rate and pulse were −1.73 and −0.77, respectively. The limits of agreement were between −14.90 and 11.33, for heart rate, and −14.25 and 12.71, for pulse. Small biases were also estimated for oxygen saturation (0.21), with limits of agreement between −6.97 and 7.39, and body temperature (0.58), with limits between −1.12 and 2.47. Concordance was low for diastolic and systolic blood pressure, with bias of 5.18 and −11.27, respectively.ConclusionsCorsano Cardiowatch 287-2B reaches good levels of concordance compared to traditional ICU monitoring for heart and pulse rates and may be a valuable solution for their less invasive monitoring, with promising results for future operationalization for oxygen saturation and body temperature. Concordance is low for blood pressure, meaning the device is currently unsuitable for use with that purpose.